Pengaruh Kepuasan Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Badan Keuangan dan Aset Daerah Kabupaten Maros - A.wafiq aziza; Akmal Umar; Dahlan (Sekolah Tinggi Ilmu Manajemen Indonesia YAPMI, 2025)
This study is intended to find out and analyze the influence of job satisfaction and work discipline on performlance at the Regional Financial and Asset Agency of MLaros Regency. This study used a quantitative approach. 92 emlployees were used as the population and research samlple with probability samlpling techniques. Data collection techniques in this research include observation, questionnaires and documlentation. The data analysis techniques were validity and reliability tests, normlality tests, hypothesis tests, regression tests (T Test) and (F Test) and coefficient of determlination tests with SPSS 26. The results of this study indicated that, partially, the variable of job satiscifation has a positve and significant effect on employee performance, the work discipline variable has a positive and significant effect on emlployee performlance and Simlultaneously job satisfaction and work discipline have a significant effect on the performlance of emlployees of financial agencies and regional assets in MLaros Regency. The R square value of 0.516 described that emlployee performlance can be explained by job satisfaction and work discipline of 51.6% while the rest is influenced by other variables that are not used by this research.